Geochemistry of the Middle Eocene Gercus Sandstone, Shaqlawa Area, Northern Iraq: Implications for Provenance, Tectonic Setting and Paleoweathering - Ali, Abbas R.; Mohammad, Omar A. M.; Ahmed, Mustafa S. (Iraqi Journal of Science, 2022)
The study of the geochemical characterization of sandstone rocks contributes to understand the nature of the source rocks, their tectonic setting and the effects of paleoclimate and paleo-weathering. Accordingly, twenty sandstone samples from the red sandstone units of the Gercus Formation were collected from the northeastern limb of Safin Anticline at Shaqlawa Area – Northern Iraq. The studied sandstone samples show depletion in major, trace elements contents, except for CaO, MgO and Ni, Co and Cr respectively, and general depletion in the rare earth elements (REE) contents. Major element geochemistry indicates that the red bed sandstones of the Gercus Formation are of an oceanic island arc (OIA) tectonic setting. On the other hand, the results revealed that the paleo-weathering of the source area of the Gercus Formation experienced intensive chemical weathering under humid and/or warm climate conditions. The maturity and paleoclimate conclusions of the studied samples suggest a low feldspar content and low values of K2O / Al2O3 ratio, which in turn resulted from the dominance of low grade metamorphic and sedimentary rock types in the source area.